Xenobiotics as a Risk Factor for Kidney and Urinary Diseases in Children and Adolescents in Modern Conditions - Zainab Sattarovna Naimova (Genius Journals, 2023)
The study of the state of health of children and adolescents under the influence of the environment is the leading direction of modern hygienic research.This is caused, on the one hand, by the increasing anthropogenic impact on nature and the associated deterioration of the ecological situation, on the other hand, by the emergence of a complex of new, mainly technogenic environmental factors - xenobiotics that can have a significant effect on humans, especially in the early stages of development of body systems. The most sensitive to the effects of both negative and positive environmental factors are children and adolescents. The organs of the genitourinary system are among the most vulnerable in relation not only to endogenous factors, but also to exogenous ones, due to the fact that most toxic substances are excreted through the kidneys.
Keywords: health; risk factors; xenobiotics; diseases of the kidneys and urinary system